Pembangunan Aplikasi Mobile Identifikasi Parkir Non Resmi berdasarkan Konsep Crowdsourcing menggunakan Geotagging - Indah Ratna Sari; Faizatul Amalia; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Parking is a necessity for the community of vehicle owners. Besides, parking areas are necessary so that vehicle users do not obstruct traffic flow as well as good city spatial rules. Therefore, the need for report information encourages the public to address the problem of parking in Malang. Because the community report to the relevant Transportation Office has not been conveyed properly so that makes the community confused to have to submit an unofficial parking report. With the development of technology, GoTindak application uses geotagging technology that can help users know the location at the time of reporting complaints or criticisms on non-official parking in the Malang city area. This research (GoTindak) utilizes a crowdsourcing feature where non-official parking report information can be directly obtained from other users. The GoTindak app contains details about the location, time, status of the report, description, and proof of photos and images. Also, there are 4 stages of report status that have not been followed up, are processed, completed, and not approved. The technique used in this study is prototyping. Further tests are validation tests, units, usability tests that use SUS (System Usability Scale) as instruments. The result of functional testing is valid status as well as the application running as per the user's needs. Usability testing that produces a value of 80.5 where the value belongs to the category is excellent and successful.